Novel Design And Implementation Of MIMO Antenna For LTE Application - Mohsen, Mowafak K.; Zakaria, Zahriladha; Abd Rahman, Tharek; Abdulhameed, Muhannad Kaml; Awang Md Isa, Azmi; Mohd Zin, Mohd Shahril Izuan; Md Saat, Mohd Shakir; Abu, Maisarah; Mohd Ibrahim, Imran; Mohamad Isa, Mohd Sa'ari; Ahmad, Asmala (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
The quest for achieving high bandwidth connectivity that renders a complete wireless system ideal for video-intensive applications at very low power consumption using multiple inputs/multiple outputs (MIMO) dual-band combo chip with high-speed is ever-growing. A newly designed structure of the MIMO antenna four ports is implemented for efficient bandwidth broadening. The bandwidth and Sparameters of the antenna are simulated and determined. The dual-band MIMO micro-strip patch antenna comprised of four ports where the ground plane is extruded on a substrate having area 125x128 mm2 and thickness 1.6 mm. The antenna is fabricated on an inexpensive FR4 with the dielectric constant of 4.5, loss tangent ~0.019 and patch thickness of 0.035 mm. The MIMO antenna with dimension 53.5x38.25 mm2 operates at 1.8 and 2.6 GHz. The proposed antenna is found to achieve good pattern diversity, low correlation coefficient, high gain, excellent directivity, and quite reasonable bandwidth in the abovementioned range, highly suitable for LTE bands application with 10 dB return loss. The CST microwave studio program is used for the simulation, and real experimental measurements are made using Agilent Technologies E5071B VNA and the equipment inside the anechoic chamber. Measurements on the prototype antenna are carried out, and characteristic evaluations are performed for comparison. The admirable features of the results suggest that our systematic approach may constitute a basis for the design and implementation of MIMO antenna for diverse LTE applications.